Hispanisation : the Impact of Spanish on the Lexicon and Grammar of the Indigenous Languages of Austronesia and the Americas. - Stolz, Thomas (Empirical Approaches to Language Typology, v. 39., 2008)
Literally hundreds of languages world-wide have experienced direct or indirect Hispanisation during the heyday of the Spanish colonial empire. The number of languages which continue to borrow from Spanish on a daily basis is considerable especially in Latin America. This volumegives the reader a better idea of the range of contact constellations in which Spanish functions as the donor language. Moreover, the contributions to this collection of articles demonstrate that it is not only possible to compare the contact-induced processes in the (Hispanised) languages of Austronesia and the America.